2017
DOI: 10.1186/s12888-017-1516-7
|View full text |Cite
|
Sign up to set email alerts
|

Community-based psychosocial interventions for people with schizophrenia in low and middle-income countries: systematic review and meta-analysis

Abstract: BackgroundThere is consensus that the treatment of schizophrenia should combine anti-psychotic medication and psychosocial interventions in order to address complex social, economic and health needs. It is recommended that family therapy or support; community-based rehabilitation; and/or self-help and support groups should be provided for people with schizophrenia in low and middle-income countries. The effectiveness of community-based psychosocial interventions in these settings is unclear.MethodsStudies eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
99
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(106 citation statements)
references
References 65 publications
6
99
0
1
Order By: Relevance
“…The subgroup meta‐analyses by types of interventions found that there were no significant effects of case management on mental health status and self‐efficacy, which are consistent with results of previous studies (Asher, Patel, & Silva, ; Vanderplasschen, Rapp, Maeyer, & Noortgate, ). Among the three included studies where case management for the homeless person was provided, two studies provided intensive case management and one provided strength‐based case management.…”
Section: Discussionsupporting
confidence: 88%
“…The subgroup meta‐analyses by types of interventions found that there were no significant effects of case management on mental health status and self‐efficacy, which are consistent with results of previous studies (Asher, Patel, & Silva, ; Vanderplasschen, Rapp, Maeyer, & Noortgate, ). Among the three included studies where case management for the homeless person was provided, two studies provided intensive case management and one provided strength‐based case management.…”
Section: Discussionsupporting
confidence: 88%
“…As CHWs form an important part of these WBOTs, they could be trained to provide community‐based psychosocial interventions for people with common mental disorders. Although a recent systematic review of community‐based psychosocial interventions in LMICs provided evidence of their feasibility, acceptability and effectiveness for reducing symptom severity and hospital readmissions among people with schizophrenia (Asher, Patel, & De Silva, ), the extent to which community‐based mental health counselling is feasible to implement and acceptable to patients with common mental disorders must still be established for the South African context.…”
Section: Discussionmentioning
confidence: 99%
“…The sample was originally recruited from persons living with schizophrenia in the community rehabilitation facility of the Shanghai Pudong New Area Mental Health Center. The following were the inclusion criteria: (1) met the diagnostic criteria for schizophrenia in the Tenth Edition of the International Statistical Classification of Diseases and Related Health Problems; (2) aged between 18 and 65; (3) were male or female; (4) had no history of head trauma, obvious intellectual disability, or other serious or uncontrolled stable physical illness; (5) had no current use (within the previous 3 months) of alcohol or drugs or a past history of dependence; and (6) had no obvious hallucinations or complaints.…”
Section: Participantsmentioning
confidence: 99%
“…Some studies have found that an increased number of hospitalizations for persons living with schizophrenia increased the psychological burden on relatives (4). The provision of antipsychotic drugs alone cannot meet the economic, social, and psychological needs of persons living with schizophrenia (5). Clinical researchers believe that the treatment of schizophrenia requires drugs combined with psychological interventions (6).…”
Section: Introductionmentioning
confidence: 99%